2018
DOI: 10.33394/jo-elt.v5i1.2297
|View full text |Cite
|
Sign up to set email alerts
|

Digital Storybook to Improve Writing Narrative: The TTW Strategy Presented and Tested

Abstract: Internet activity is an ICT (Information, Communication and Technology) provides opportunities for students in learning through digital story books that are presented in an interesting way and directly contribute to the improvement of the ability to write narrative. The think-talk-write strategy (TTW) is based on the development of thinking skills, verbal and written communication. The flow of progress of this strategy starts from the involvement of students in thinking or dialogue with themselves after the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This is in line with the view of (Djamdjuri & Wulandari, 2018;Irawan et al, 2020;Wang & Chen, 2020). For the question number 7, it proves that easy to access was one of the features of digital media (Handayani et al, 2020;Irawati, 2018;Tóth, 2021). Furthermore, the answers from the three respondents on the interview question number 3 show the importance of communication and interaction between lecturers and students, both when learning is carried out online and offline.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in line with the view of (Djamdjuri & Wulandari, 2018;Irawan et al, 2020;Wang & Chen, 2020). For the question number 7, it proves that easy to access was one of the features of digital media (Handayani et al, 2020;Irawati, 2018;Tóth, 2021). Furthermore, the answers from the three respondents on the interview question number 3 show the importance of communication and interaction between lecturers and students, both when learning is carried out online and offline.…”
Section: Discussionsupporting
confidence: 80%
“…Digital media is an activity of combining narrative stories with digital content in which there are images, sound, music, and videos so that they can produce an interesting short film that can be made in an instructional format for teaching, persuasive, historical, or as a reflection activity (Yi et al, 2019). From the statement above, it can be concluded that multimodalbased digital media books are widely used because they have several advantages, namely easy access and can support the teaching and learning process (Irawati, 2018). Many education experts believe that digital media can be applied to several subjects, and can accommodate a variety of student learning styles (Moody, 2010;Wu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many experts claim that digital storybook can be used as an effective learning medium (Nunan, 2010). One example, Irawati (2018) applied this digital storybook to improve students' narrative writing skills and also succeeded in increasing student scores by using digital storybooks as a media to improve students' skills. In addition, Moody, in Irawati (2018) stated that several reasons why educators can use digital storybook are: because it is very accessible, efficient, and cheap with many titles provided.…”
Section: Introductionmentioning
confidence: 99%
“…Digital storybooks are online media that can convey a series of events in the form of words, which can contain pictures, sounds, and music by adding everything to it with one effective purpose. Irawati (2018) mentioned that the use of digital storybooks is highly recommended to improve narrative writing skills. This is in line with Heriyana & Maureen (2018) that proposed that the use of collaborative DST-based tasks significantly improves students' writing skills.…”
Section: Introductionmentioning
confidence: 99%